2006
DOI: 10.1681/asn.2006080938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atorvastatin on Inflammatory and Fibrinolytic Parameters in Patients with Chronic Kidney Disease

Abstract: Although substantial evidence suggests that treatment of dyslipidemia with statins reduces mortality and morbidity that are associated with cardiovascular disease, only a few studies have examined the efficacy of statins on inflammatory and fibrinolytic status in patients with chronic kidney disease (CKD). A 6-mo, prospective, randomized study was designed to assess the efficacy of atorvastatin in reducing circulating inflammatory and fibrinolytic parameters in patients with CKD. Sixty-six patients with CKD (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 28 publications
6
49
0
1
Order By: Relevance
“…Finally, statins may also play a vital role in controlling inflammation in CKD. In 66 adults with stages 2-4 CKD and hyperlipidemia, treatment with atorvastatin resulted in a reduction of both serum lipid levels and inflammation, the latter measured by CRP, TNF-α, and IL-1β; in comparison, no changes were observed in the untreated patients [41].…”
Section: Attenuation Of Inflammation In Ckd: Effect On Progressionmentioning
confidence: 89%
“…Finally, statins may also play a vital role in controlling inflammation in CKD. In 66 adults with stages 2-4 CKD and hyperlipidemia, treatment with atorvastatin resulted in a reduction of both serum lipid levels and inflammation, the latter measured by CRP, TNF-α, and IL-1β; in comparison, no changes were observed in the untreated patients [41].…”
Section: Attenuation Of Inflammation In Ckd: Effect On Progressionmentioning
confidence: 89%
“…In agreement with our data, a recent study by Lorenzen et al [29] reported a positive association between pOPN and the vascular inflammation markers IL-6 and CRP in hypertensive patients. Furthermore, we observed that the use of statins (which have been shown to have major anti-inflammatory effects and to decrease IL-6 levels in both nonrenal patients with coronary artery disease [30,31] or essential hypertension [32] and in CKD patients [33,34]) was more frequent in the group of patients with lower pOPN levels. It is noteworthy that this negative association between statin treatment and pOPN has also been observed in nonrenal populations [12,29,35].…”
Section: Discussionmentioning
confidence: 99%
“…Statins are also significantly effective to decrease lipid levels in nephrotic syndrome; however, their long-term effects and their effects on cardiovascular complications should be determined and require further studies [53]. Other than anti-lipidemic effects, Goicoechea et al [54] demonstrated the effect of atorvastatin on inflammatory parameters in CKD patients in a 6-month prospective randomized study and they showed that statin therapy can decrease the inflammatory parameters in addition to its anti-lipidemic effects. In addition, Kanbay et al [55] showed that statins can improve endothelial dysfunction, which ­occurs due to oxidative stress and significantly decreased systolic and diastolic blood pressure in CKD patients.…”
Section: Treatment Strategies For Dyslipidemia In Ckd: How To Improvementioning
confidence: 99%